Site response studies in Mumbai using (H/V) Nakamura technique - Surve, G.; Mohan, G. (My University, 2010)
The importance of characterizing the site effects in urban areas, especially Mumbai, the commercial capital of India, with a quarter of land below sea level, is well realized. Mumbai is built on a cluster of seven basaltic islands that were merged together through reclamation of land from the Arabian Sea. Due to rapid urbanization, the demarcation between reclaimed areas and original islands is blurred. A pilot study is undertaken to investigate and characterize the local site effects at 27 locations in Mumbai. The Nakamura technique is used to estimate the fundamental frequency of soft soils at each site, characterized by the ratio (H/V) of the Fourier spectra of the horizontal and vertical components of ambient noise measurements made with a 3-component short period (1 Hz) seismograph. Validation of peak frequency was done using both pre-event and event data. The peak amplification was also validated through measurements at a 10-m exposed soil section and over a soil dump. Overall, the site responses correlate well with the local geology and the lithologs obtained at 40 boreholes at 8 locations The reclaimed areas are characterized by resonance frequencies ranging from 3.3 to 4.6 Hz with significant peak amplification (>4) in contrast to hard rock sites that do not exhibit peak amplification. The hard rock sites with soil cover exhibit peak amplification in the frequency range 3.3–10.5 Hz indicating large variations in soil thickness. The H/V curves at most sites exhibit clear single peaks with large amplitude, which could be associated with sharp discontinuities corresponding to a uni-model of a single layer with large velocity contrast overlying the basement. The low resonance frequencies together with large amplification of site responses enable identifying and demarcating reclaimed areas that form important inputs in the seismic microzonation of Mumbai.
Keywords: Amplification; Mumbai; Nakamura; Reclaimed land; Site response